(3HQGgjf GdYbhd aj cTa CSQGQ JgPjH GdCUhds - (3GdThjgj, GdMejOj, GdfLaj, GdMScj, GdMdj, eMeO Hf jhfS Hf QGVj, J (B1240(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3SdWGfG jWGY jQLY Edjg GdcJGH hGdSfI hGdELeGY hLYd GdSfI dMcGe GdTQY(B...s
(3BNQgG (B:s
(3adG jJUhQ ajg GdJNjjQ dYOe GdJYOO ajg (B... (3eQLY Edi bhd GdeYJRdIs
(3JHUQI GdYfhGf (B:s
(3aj GdCYdGe(B: (3HQGgjf GdYbhd aj TQM JgPjH GdGUhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B7(3, U(B160s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B197s
(3GdCYdGe(B: (3L(B7(3, U(B160s
Keywords: (3CUhd Gdabgs